Crushing, stirring, mixing, kneading machine components

By using metal cermets of Ti, Mo, W, C, and Co in the crushing, stirring, mixing and mixing mechanisms to form a specific structure, the problem of insufficient impact resistance and wear resistance in the prior art is solved. It achieves efficient crushing, stirring, mixing and mixing performance, and reduces the equipment load.

CN115943222BActive Publication Date: 2024-12-20NIPPON TUNGSTEN CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180044645.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-02-10
Filing Date
2021-07-28
Publication Date
2024-12-20
Estimated Expiration
2041-07-28

AI Technical Summary

Technical Problem

The existing metal cermets are insufficient in impact resistance and wear resistance in crushing, stirring, mixing and mixing mechanisms, resulting in easy destruction of components and short life. The high specific gravity of superhard alloys leads to an increase in the load of the drive device and the rotation shaft. Problems such as deflection.

Method used

Metal cermets of Ti: 20-45%, Mo: 5-35%, W: 6-30%, C: 5-15%, Co: 10-50% are used, and are molded by wet or dry type mixing and pressing, and Sintered under a vacuum, reduction and inactive atmosphere between 1300 and 1700°C to form a core phase mainly composed of (Ti, Mo, W) (C, N) and a metal phase, with an average particle size The diameter is less than 3 μm, avoiding the existence of WC and Mo2C.

Benefits of technology

It has achieved a significant improvement in lightweight, magnetic, impact resistance and wear resistance, extended the life of crushing, stirring, mixing and mixing mechanism parts, and is suitable for twin-screw extruders, bead mills and other equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115943222B_ABST
    Figure CN115943222B_ABST
Patent Text Reader

Abstract

The present invention provides a pulverizing, stirring, mixing, and kneading machine component that is lightweight, has excellent impact resistance and wear resistance, and further has magnetic properties, and the service life of these components is prolonged. That is, the present invention provides a pulverizing, stirring, mixing, and kneading machine component containing metal ceramics, by mixing raw materials in a manner such that the mass ratio of each element is Ti: 20-45%, Mo: 5-35%, W: 6-30%, C: 5-15%, Co: 10-50%, and the total of Co and Ni exceeds 25% and is 50% or less, mixing them to obtain a mixed powder, pressing the mixed powder to obtain a pressed body, and sintering the pressed body to obtain a metal ceramic. The metal ceramic has three phases, namely, a core phase 2 with TiCN as the main component, an annular phase 3 with (Ti, Mo, W) (C, N) as the main component, and a metal phase 4. The average particle size of the hard phase composed of the core phase and the annular phase in cross-sectional microstructure observation is less than 3μm, and no WC phase and Mo2C phase are observed by SEM observation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a pulverizing, stirring, mixing and kneading machine component including a cermet having excellent impact resistance and wear resistance. Background Art

[0002] Various material design methods have been proposed for cermets having excellent impact resistance and wear resistance.

[0003] Patent Document 1 discloses a method for producing a cermet that is highly strengthened even when the TiN / TiC ratio is 3 / 7 to 7 / 3 by using a three-step sintering method of temporary sintering in a reduced pressure nitrogen atmosphere, HIP treatment, and final heat treatment in a reduced pressure nitrogen atmosphere to eliminate pores and binding phase pools. Such a carbonitride-based cermet is used for cutting tools such as milling.

[0004] Patent Document 2 discloses a cermet that has a two-phase structure of a core composed of a hard phase and a ring of a peripheral structure having toughness, and a third phase rich in WC having excellent toughness is formed around the central core, thereby further increasing the toughness. Compared with conventional cermets, this cermet has improved bending strength and fracture toughness without reducing wear resistance and hardness, and can be widely used as a tool for machine tools, not to mention parts and components requiring wear resistance and toughness.

[0005] Patent Document 3 discloses a cermet that increases the amount of nitrides and further controls the hard phase grain size to be coarser, thereby strengthening the binder phase to improve impact resistance, wear resistance, and thermoplastic deformation resistance. In this way, the problem of shortened life due to defects caused by thermal cracks in cutting tools that are intermittently subjected to severe thermal shocks is solved.

[0006] Patent Document 4 discloses a cermet for a heat transfer roller, which contains 5 to 50% TiC, 1 to 25% of one or more of Mo2C, TaC, VC, Cr3C2, NbC, ZrC, and HfC, and a total of 5 to 40% Ni and Co, and the average particle size of the TiC is 1.5 to 15 μm, and the particle size of the WC is 3 to 15 μm. This cermet can suppress the development of surface cracks, which is the biggest problem of hot rolling, by using coarse hard particles, and can increase the life of the heat transfer roller.

[0007] Patent Document 5 discloses that the lattice constant of the bonding phase containing Ni and Co as main components is controlled within The following can improve the heat crack resistance and increase the life of high-speed cutting tools.

[0008] In addition, in recent years, the demand for lightweight, high-functional resin materials has increased. In order to improve their properties, the production of reinforced resin materials that are highly filled with fillers such as glass fiber and inorganic powder has increased. Along with this, the reduction in production efficiency caused by severe wear of components of crushing, stirring, mixing, and kneading machines has become a problem. In resins for precision electronic components, metal contamination caused by wear of components is a problem. Not only does it need to be removed by magnetic separation, but as a fundamental countermeasure, it is necessary to improve the wear of components that are the source of mixing.

[0009] Nitrided steel is often used as components of pulverizing, stirring, mixing, and kneading machines. However, alloy tool steel is known to be suitable for applications requiring higher wear resistance, and superhard alloy is suitable for use under more severe usage conditions.

[0010] Patent document 6 discloses the manufacture of a kneading disk as follows: by using discharge plasma sintering to sinter and join multiple disk components made of a superhard alloy having higher wear resistance than conventional alloy tool steels, grinding and cutting of a kneading disk having a complex shape becomes easy and wear resistance is excellent.

[0011] Patent Document 7 discloses a cemented carbide molding member that is formed by pressure-sintering cemented carbide segments in the axial direction, thereby preventing deformation of a screw or barrel having an elongated shape, thereby enabling long-term continuous use.

[0012] Prior art literature

[0013] Patent Literature

[0014] Patent Document 1: Japanese Patent Application Laid-Open No. 61-003852

[0015] Patent Document 2: Japanese Patent Application Laid-Open No. 62-196352

[0016] Patent Document 3: Japanese Patent Application Laid-Open No. 63-109139

[0017] Patent Document 4: Japanese Patent Application Laid-Open No. 2-66135

[0018] Patent Document 5: Japanese Patent Application Laid-Open No. 7-112313

[0019] Patent Document 6: Japanese Patent Application Laid-Open No. 11-10709

[0020] Patent Document 7: Japanese Patent Application Publication No. 2011-88410

[0021] Non-patent literature

[0022] Non-patent document 1: Kawabata, Fujimura, and Chitoku, "Powder and Powder Metallurgy", Vol. 29, No. 1 (1980), 30-34. Summary of the invention

[0023] Problems to be solved by the invention

[0024] When the metal ceramic disclosed in Patent Document 1 is used in components of a crushing, stirring, mixing, or kneading machine, since the metal content is relatively small, the impact absorption caused by elastic deformation becomes insufficient, and the toughness of the raw material itself is also low, so it is possible to cause damage due to the impact caused by contact between the components during operation.

[0025] In the metal ceramic disclosed in patent document 2, due to the presence of WC single particles, hard WC particles are easily the starting point of destruction, and there is concern about poor impact resistance. Therefore, as mentioned above, due to the contact of components in the work of crushing, stirring, mixing, and mixing machine components, cracking is likely to occur. Furthermore, due to the presence of a large amount of WC with a high specific gravity, the weight of the component becomes heavier, and when applied to rotating device components, shaft shaking and increased load on the drive device are likely to occur.

[0026] The metal ceramic disclosed in Patent Document 3 is intended for use in cutting tools. However, due to the small amount of metal phase and the presence of separate particles of WC and Mo2C in the metal phase, it cannot be used as a component of a crushing, stirring, mixing, or kneading machine because of its insufficient toughness and impact resistance.

[0027] The metal ceramic disclosed in Patent Document 4 has WC coarse-grained powder added for the purpose of suppressing thermal cracking. However, in the components of pulverizing, stirring, mixing and kneading machines that produce abrasive wear, the lack of WC coarse-grained powder increases the volume reduction and shortens the life of the components.

[0028] The cermet disclosed in Patent Document 5 is based on the premise of being used in cutting tools, and therefore has a small amount of metal phase, insufficient impact resistance and toughness, and is therefore not suitable for use as a component of a pulverizing, stirring, mixing, or kneading machine.

[0029] The kneading disk and molding components disclosed in Patent Documents 6 and 7 use a highly wear-resistant superhard alloy, thereby increasing the life of the components. However, conventional crushing, stirring, mixing, and kneading machines are designed based on the premise that components made of steel materials are installed. Superhard alloy components are not suitable for use as replacements for components made of steel materials due to their high specific gravity, increased load on the drive device side, deflection of the rotating shaft, and other unresolved problems.

[0030] The present invention has been made to solve the above-mentioned problems, and its object is to provide pulverizing, stirring, mixing and kneading machine components which are lightweight, excellent in impact resistance and wear resistance, and further have magnetism, and to extend the life of these components.

[0031] Means for solving problems

[0032] The present invention solves the above-mentioned problems by providing the following cermet for components of a pulverizing, stirring, mixing, and kneading machine, wherein the cermet is obtained by the following steps: powders arbitrarily selected from Ti or a Ti compound, Mo or a Mo compound, W or a W compound, Co or a Co compound, Ni or a Ni compound, and carbon are used as raw materials, and these powders are wet or dry mixed in such a manner that the mass ratio of each element is Ti: 20 to 45%, Mo: 5 to 35%, W: 6 to 30%, C: 5 to 15%, Co: 10 to 50%, and the total of Co and Ni is more than 25% and less than 50%, thereby obtaining The invention relates to a method for preparing a metal ceramic comprising: preparing a mixed powder; pressing the mixed powder at a pressure of 50 to 300 MPa to obtain a pressed body; and sintering the pressed body at 1300 to 1700°C in an atmosphere of vacuum, reduction, inert gas, hydrogen or nitrogen. The metal ceramic comprises three phases: a core phase with TiCN as the main component, an annular phase with (Ti, Mo, W) (C, N) as the main components and a metal phase, wherein the average particle size of the hard phase composed of the core phase and the annular phase in cross-sectional microstructure observation is less than 3 μm, and no WC phase or Mo2C phase is observed by SEM observation.

[0033] Effects of the Invention

[0034] The cermet obtained in the present invention, which has magnetism, is lightweight, and has greatly improved wear resistance and impact resistance, can extend the life of components of pulverizing, stirring, mixing, and kneading machines that are subject to severe wear.

[0035] Specifically, the present invention can be suitably used as a pulverizing, stirring, mixing and kneading machine component, such as a screw element for a twin-screw extruder, a barrel, a pulverizing pin of a pin mill device, a paddle of a mixer, a powder processing device component such as a bead mill, and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a schematic diagram of the cross-sectional structure of the cermet used in the pulverizing, stirring, mixing and kneading machine components of the present invention.

[0037] Figure 2 This is a schematic diagram of the cross-sectional structure of the cermet used in the pulverizing, stirring, mixing, and kneading machine component of the present invention, wherein the cermet has a phase containing relatively more Mo and W in the annular phase.

[0038] Figure 3 This is a SEM observation image of the cermet used in the pulverizing, stirring, mixing, and kneading machine components of Example 1. DETAILED DESCRIPTION

[0039] The pulverizing, stirring, mixing and kneading device components of the present invention can be implemented as follows.

[0040] First, a powder arbitrarily selected from Ti or a Ti compound, Mo or a Mo compound, W or a W compound, Co or a Co compound, Ni or a Ni compound and carbon is used as a raw material, so that the mass ratio of each element is Ti: 20-45%, Mo: 5-35%, W: 6-30%, C: 5-15%, Co: 10-50%, and the total of Co and Ni is more than 25% and less than 50%.

[0041] For example, the compound of Ti may be any form of carbide, nitride, carbonitride, or composite carbonitride such as TiC, TiN, TiCN, (Ti, Mo) (C, N), and (Ti, W) (C, N). The same is true for Mo, W, Co, and Ni.

[0042] Then, they are wet or dry mixed to obtain a mixed powder, the mixed powder is pressed under a pressure of 50 to 300 MPa to obtain a pressed body, and the pressed body is sintered at 1300 to 1700°C in a vacuum, reduction, inert gas, hydrogen or nitrogen atmosphere to obtain a pulverizing, stirring, mixing and kneading machine component containing metal ceramics. The metal ceramic has three phases: a core phase, an annular phase and a metal phase. The specific design of each phase is described below. It should be noted that in the following description, the mass ratio of each element is the mass ratio of the raw material stage.

[0043] (Core phase and ring phase design)

[0044] By making C 5-15%, a hard phase composed of a fine core phase and annular phase with improved sinterability is formed. When C is less than 5%, a sufficient volume of core phase and annular phase is not generated, and wear resistance is reduced. On the other hand, when more than 15% of C is added, a free carbon phase is generated, and mechanical properties (strength, hardness, impact resistance) are greatly reduced.

[0045] When N is added, it can be added arbitrarily within the range of more than 0 and less than 5%. By adding N, the thickness of the ring phase tends to be reduced, and the wear resistance and impact resistance are improved. In addition, by making N 5% or less, it is possible to suppress the residual pores in the alloy caused by nitrogen generated during sintering, and it is possible to achieve improvement in mechanical properties.

[0046] Furthermore, C:N is preferably 7:3 to 10:0. By setting the C:N ratio within this range, good wettability between the metal phase and the hard phase composed of the core phase and the ring phase is maintained, and the density is improved.

[0047] Mo is mixed in the range of 5-35% and W is mixed in the range of 6-30%. TiCN forming the core phase has poor wettability with Co and Ni forming the metal phase, but the ring phase generated by adding Mo2C and WC can improve the wettability of the hard phase composed of the core phase and the ring phase. As a result, the sinterability of the material is improved and the mechanical properties can be improved.

[0048] In addition, the wear resistance can be further improved by adding W. This is because the hard phase composed of the core phase and the ring phase is solid-solution strengthened by W atoms, and the hard phase is less likely to be destroyed during abrasive wear.

[0049] When the total content of Mo and W is 35% or less, alloys of W and Co, Mo and Co, or W, Mo, and Co are not formed, and the impact resistance is further improved.

[0050] (Design of Metal Phase)

[0051] The total amount of Co and Ni exceeds 25% and is less than 50%. When the metal content is less than this range, the impact resistance becomes insufficient. When the metal content is more than this range, the wear resistance decreases and the wear of the components of the crushing, stirring, mixing and kneading machine becomes severe.

[0052] In addition, Co is set to 10 to 50%. By setting Co, which has mechanical properties (hardness and wear resistance) superior to Ni, to this range, the mechanical properties of the components of the pulverizing, stirring, mixing and kneading machine can be improved and the service life can be prolonged.

[0053] Furthermore, cermets containing 10% or more of Co have sufficient magnetic properties for magnetic separation. Magnetic separation is used to detect foreign matter in materials caused by chips of components in pulverizing, stirring, mixing, and kneading machines.

[0054] The pulverizing, stirring, mixing and kneading device component of the present invention can be produced by the following production method as an example.

[0055] (Manufacturing method)

[0056] When manufacturing the pulverizing, stirring, mixing, and kneading device component of the present invention, the following steps (processes) are included.

[0057] That is, the step of wet or dry mixing powders arbitrarily selected from Ti or a Ti compound, Mo or a Mo compound, W or a W compound, Co or a Co compound, Ni or a Ni compound, and carbon as raw materials so that the mass ratio of each element is Ti: 20 to 45%, Mo: 5 to 35%, W: 6 to 30%, C: 5 to 15%, Co: 10 to 50%, and the total of Co and Ni is more than 25% and less than 50% to obtain a mixed powder;

[0058] The mixed powder is pressed under a pressure of 50 to 300 MPa to obtain a pressed body; and

[0059] The step of sintering the compact at 1300-1700° C. in any one of vacuum, reduction, inert gas, hydrogen or nitrogen atmosphere.

[0060] In the case of wet mixing, a volatile solvent such as ethanol is used as a solvent, and the slurry is dried by vacuum standing drying or spray drying. At this time, the particle size of the particles forming the core phase and the ring phase after the raw materials are mixed (hereinafter referred to as "the particle size before sintering") is fully micronized in such a way that the average particle size of the hard phase after sintering is less than 3μm. The particle size before sintering can be less than 2.0μm, preferably less than 1.5μm, more preferably less than 1.0μm, and further preferably less than 0.6μm. Usually, the particles are grown by sintering. If the particle size before sintering is less than 2.0μm, the generation of coarse hard particles can be suppressed. When it is less than 1.5μm, the technical feature of making the average particle size of the hard phase after sintering less than 3μm can be easily satisfied. If it is less than 1.0μm, the average particle size of the hard phase after sintering becomes smaller, and the wear resistance is improved. Furthermore, if it is less than 0.6μm, it can be sintered at a lower temperature, which can improve the wear resistance.

[0061] The obtained fine particle powder is mixed with a resin component that becomes a molding binder and granulated. Spray drying may also be used for granulation.

[0062] The granulated powder is pressed and molded by a die press or an isostatic press at 50 to 300 MPa. After molding, intermediate processing can be performed as needed.

[0063] As for the sintering conditions, the formal sintering is carried out in a vacuum or gas atmosphere at 1300-1700°C. Degreasing and pre-sintering steps can be introduced before the formal sintering, and intermediate processing can be introduced at each stage after degreasing and pre-sintering as needed. The degreasing and pre-sintering steps can be carried out continuously, or the degreasing and pre-sintering steps and formal sintering can be carried out continuously. When degreasing and pre-sintering are carried out, they are carried out in a vacuum or gas atmosphere at 600-1000°C. Furthermore, hot isostatic pressing (hot water pressure press) can be carried out as needed.

[0064] Finally, the final shape is obtained by machining or electrical machining to obtain the target pulverizing, stirring, mixing and kneading machine components.

[0065] (Organization of metal ceramics used for crushing, stirring, mixing and kneading machine components)

[0066] The structure of the cermet used in the present invention was confirmed by cross-sectional observation using a SEM.

[0067] As in Figure 1 As shown schematically in the cross-sectional structure 1, the metal ceramic has three phases, namely, a core phase 2 with TiCN as the main component, an annular phase 3 with (Ti, Mo, W) (C, N) as the main component and a metal phase 4, which exists in a manner covering the periphery of the core phase 2. The average particle size of the hard phase composed of the core phase and the annular phase in the cross-sectional structure observation is less than 3 μm, and the metal ceramic does not contain WC phase and Mo2C phase in principle. In the case of WC phase and Mo2C phase, in SEM (scanning electron microscope) observation, in addition to the core phase and the annular phase, particles with different brightness exist in the metal phase. In the case of being unable to judge, an analysis based on EPMA (electron probe microanalyzer), EDX (energy dispersive X-ray analysis), and XRD (X-ray diffraction) is performed to comprehensively judge the presence or absence of WC phase and Mo2C phase. In the case of irregular observation, in the 10,000-fold observation field of view, there are less than 1 particle larger than 1 μm, and less than 5 particles larger than 0.3 μm. It should be noted that in the present invention, “no WC phase and Mo2C phase were observed by SEM observation” also includes the case where there are 1 or less particles larger than 1 μm and 5 or less particles larger than 0.3 μm in the above-mentioned 10,000-fold observation field.

[0068] By adopting the above-mentioned configuration, a material having high impact resistance and wear resistance can be obtained.

[0069] In addition, the above-mentioned cermet has the following characteristics.

[0070] (Core Phase)

[0071] The core phase is a hard phase having TiCN as a main component and has high hardness.

[0072] (Annular Phase)

[0073] The ring phase exists in a manner covering the periphery of the core phase, and has (Ti, Mo, W) (C, N) as main components. Figure 2 As shown, the annular phase may have two phases, namely, a phase with relatively more Mo and W components and a phase with relatively more Ti. When the annular phase is two phases, the hardness of the annular phase is improved, and the wear resistance is further improved.

[0074] (Particle size)

[0075] The average grain size of the hard phase composed of the core phase and the ring phase is less than 3 μm. The average grain size can be calculated from the following Fillman formula (Formula 1) by SEM observation of the cross-sectional structure of the cermet.

[0076] [Mathematical formula 1]

[0077] d m =(4 / π)×(N L / N S ) (Formula 1)

[0078] N L =n L / L (Formula 2)

[0079] N S =n S / S (Formula 3)

[0080] In (Formula 1), d m represents the average particle size, π represents the circumference, N L represents the number of particles per unit length hit by any straight line on the cross-sectional tissue, N S represents the number of particles contained in any unit area, where n L represents the number of particles hit by an arbitrary straight line on the cross-sectional structure, L represents the length of an arbitrary straight line on the cross-sectional structure, and (Formula 3) wherein n S represents the number of particles contained in an arbitrary measurement area, and S represents the area of ​​an arbitrary measurement area.

[0081] By making the average particle size of the hard phase composed of the core phase and the annular phase less than 3 μm, the mechanical properties and impact resistance are improved, so it is not easy to be broken when an impact is applied due to crushing, stirring, mixing, contact of components during the operation of the mixer, etc. In particular, by making the average particle size of the hard phase less than 1.5 μm, the hardness is further improved and the wear resistance is also improved. When the average particle size of the hard phase is more than 3 μm, the unit of particle shedding during abrasive wear becomes larger, so the wear resistance is significantly reduced.

[0082] (proportion)

[0083] The specific gravity of the components of the crushing, stirring, mixing, and kneading machine involved in this embodiment is 9 or less. The crushing, stirring, mixing, and kneading machine has been designed based on the installation of components made of steel materials in the past. Therefore, when the specific gravity of the components exceeds 9, it causes the deflection of the rotating shaft and the increase of the load on the drive device side. When the specific gravity is 8 or less, it can be processed in the same way as steel materials. When the specific gravity is 7.5 or less, it becomes lighter than steel materials, which can increase the degree of freedom of device design.

[0084] The metal ceramics having the above characteristics have wear resistance and impact resistance as high as superhard alloys, but have the same specific gravity as steel materials and are magnetic. By using the material as a component of a crushing, stirring, mixing, or kneading machine, it is possible to suppress damage caused by contact between components and wear of components during use, thereby extending the life of the components.

[0085] Example

[0086] First, the raw material powders shown in Example 1 in Table 1 were pulverized and mixed using an attritor or a ball mill using ethanol as a solvent. The obtained slurry was dried in a vacuum, mixed with paraffin as a binder, and then pressed to produce a compact.

[0087] The compact is preliminarily sintered at 800° C. in an atmospheric pressure hydrogen atmosphere, and then fully sintered at 1400° C. in a vacuum atmosphere, thereby obtaining a cermet used in the pulverizing, stirring, mixing, and kneading machine component of the present invention.

[0088] The average particle size of the cermet obtained in Example 1 calculated by the above-mentioned Fillman formula was 1.12 μm.

[0089] In Example 2 and subsequent Examples and Comparative Examples, sintering was performed at the lowest temperature at which the highest density was obtained within the range of 1300 to 1500° C. Other conditions were the same as those in Example 1.

[0090] In addition, in all Examples and Comparative Examples except Comparative Example 6, the average grain size of the hard phase composed of the core phase and the ring phase was less than 1.5 μm.

[0091] Furthermore, the constituent components of the metal ceramic cross-sectional structure were observed by SEM observation, and the existence of Mo2C phase and WC phase was not confirmed in all the examples. In addition, in all the examples, a phase with relatively more Mo component and W component existed in the annular phase.

[0092] The element composition ratio of the metal ceramic structure as a whole deviates greatly from the raw material composition, and the coefficient of determination of the composition ratio of the raw material composition to the sintered metal ceramic is low, and it is impossible to quantify it correctly. For reference, the quantitative analysis results of the metal ceramic of Example 1 using EPMA and EDX are shown in Table 3, and the deviation from the raw material composition can be confirmed. As a reason for this, it is believed that the change in the lattice state caused by the solid solution formation of each constituent element has an impact. As shown in the above-mentioned non-patent document 1, it is known that it is difficult to quantify the alloy composition of metal ceramic materials in past studies, and it is difficult to perform accurate quantification.

[0093] Thus, in the present invention, it is impossible or generally impractical to directly identify the object based on its structure or characteristics, and there are so-called "impossible and impractical situations" in the present invention.

[0094] [Table 1]

[0095]

[0096] [Table 2]

[0097]

[0098] [Table 3]

[0099]

[0100] Next, the mechanical properties of the produced cermet were evaluated by the following measuring methods.

[0101] *Specific gravity...Archimedes method (standard: JIS Z 8807)

[0102] *Hardness···Vickers hardness test (standard: JIS Z 2244)

[0103] *Abrasion resistance···Rubber wheel test (standard: ASTM G65)

[0104] *Impact resistance···Charpy impact test (standard: JIS Z 2242)

[0105] *Magnetic properties…Saturation magnetization measurement

[0106] Table 4 shows the properties of the cermets in Examples of the present invention and Comparative Examples.

[0107] [Table 4]

[0108]

[0109] ※Superhard wear volume (mm 3 ) / wear volume of sample (mm 3 )

[0110] In all examples, the specific gravity was kept below the target of 9, and the wear resistance was superior to that of cemented carbide (JIS classification: V40 equivalent material), showing excellent properties. In addition, the impact resistance was 6J / cm2, which was difficult to achieve with conventional metal ceramics. 2 above.

[0111] Compared with Example 1, Examples 2 and 6 show particularly high wear resistance.

[0112] In Example 2, the amount of Mo added is relatively large, and W is co-added to improve the hardness. Although the amount of metal is the same as that of Example 1, high wear resistance is exhibited.

[0113] In Example 6, although the Charpy impact value is less than 10 J / cm 2 , but the wear resistance is more than 200% compared with super cemented carbide (JIS classification: V40 equivalent material). This is an example of showing very high wear resistance by suppressing the metal content to the minimum required.

[0114] Comparative Example 1 has a larger amount of Mo added than the present invention, and shows a very high value for wear resistance. However, the Charpy impact value is low, and there is a possibility of breakage, so it cannot be used as a component of a pulverizing, stirring, mixing, or kneading machine.

[0115] In Comparative Example 2, since the amount of W added was excessive, a WC phase was formed, and the wear resistance was significantly reduced.

[0116] In Comparative Examples 3 and 7, only Ni was used as the metal phase. Although the amount of Mo, W, and metal phase in these samples was within the range, the metal phase was only Ni, so the hardness, wear resistance, and magnetic properties showed low values. It can be said that Co addition is necessary for the performance of magnetic properties.

[0117] When the addition amounts of Mo and W are small as in Comparative Example 4, the wear resistance shows a low value.

[0118] In Comparative Example 5, the metal phase amount (total of Co and Ni) is 24%, which is lower than the lower limit of the present invention. Like general cermets mainly used for tools, although the wear resistance is high, the fracture toughness, flexural strength and Charpy impact value are low.

[0119] Comparative Example 6 is a sample produced by mixing raw materials without pulverizing them in the same composition as in Example 1. After sintering, the average particle size of the hard phase composed of the core phase and the ring phase exceeded 3 μm, so the hardness and impact resistance decreased.

[0120] Although the metal phase amount is within the range, the Co amount which has high mechanical properties such as hardness and wear resistance is insufficient in Comparative Examples 8 to 10, so the wear resistance is reduced. The magnetic properties are also lower than those of superhard materials.

[0121] exist Figure 3 ] is a SEM observation image of the cermet of Example 1. The darkest part is the core phase, the darker part is the ring phase, and the lightest part is the metal phase.

[0122] Description of Reference Numerals

[0123] 1 Cross-sectional structure of metal ceramics

[0124] 2 core phase

[0125] 3 Ring phase

[0126] 4 Metal phase

[0127] 5 Phases with relatively more Mo and W

Claims

1. Contains metal ceramic crushing, stirring, mixing, kneading machine components, in, The metal ceramic is obtained by the following steps: A step of wet or dry mixing powders arbitrarily selected from Ti or a Ti compound, Mo or a Mo compound, W or a W compound, Co or a Co compound, Ni or a Ni compound, and carbon as raw materials to obtain a mixed powder in a manner consisting of Ti: 20-45%, Mo: 5-35%, W: 6-30%, C: 5-15%, Co: 10-50%, Co and Ni total exceeding 25% and not exceeding 50%, and N exceeding 0 and not exceeding 5% in terms of mass ratio of each element; The step of pressing the mixed powder at a pressure of 50 to 300 MPa to obtain a pressed body; and The step of sintering the pressed body in a vacuum or gas atmosphere at 1300-1700°C, The cermet has three phases: a core phase mainly composed of TiCN, a ring phase mainly composed of (Ti, Mo, W) (C, N) and existing around the core phase, and a metal phase. The average particle size of the hard phase consisting of the core phase and the ring phase in the cross-sectional microstructure observation is less than 3 μm. No WC phase and Mo were observed by SEM. 2 Phase C.

2. The pulverizing, stirring, mixing and kneading machine component comprising metal ceramics according to claim 1, in, The mass ratio of C to N in the raw material is C:N=7:3-10:0, wherein N is not zero.

3. The pulverizing, stirring, mixing and kneading machine component containing metal ceramics according to claim 1 or 2, in, The ring-shaped phase has two phases, a phase containing relatively more Mo and W and a phase containing relatively more Ti.

4. The pulverizing, stirring, mixing and kneading machine component containing metal ceramics according to claim 1 or 2, in, The gas atmosphere is a reducing atmosphere.

5. The pulverizing, stirring, mixing and kneading machine component containing metal ceramics according to claim 1 or 2, in, The gas atmosphere is an inert gas atmosphere.

6. The pulverizing, stirring, mixing and kneading machine component containing metal ceramics according to claim 1 or 2, in, The gas atmosphere is a hydrogen atmosphere.

7. The pulverizing, stirring, mixing and kneading machine component containing metal ceramics according to claim 1 or 2, in, The gas atmosphere is a nitrogen atmosphere.

Citation Information

Patent Citations

  • Kneading disk and manufacture of kneading disk

    JP1999010709A

  • Ultra hard material for molding and molding machine carrying the ultra hard material

    JP2011088410A

  • Superfine metalloceramics material and preparation method thereof

    CN105734382A

  • Submicron grain Ti(C, N)-base cermet and its prepn process

    CN1609052A